Prenylated Coumarins of the Genus Citrus: An Overview of the 2006-2016 Literature Data - Genovese, Salvatore; Taddeo, Vito A.; Epifano, Francesco; Fiorito, Serena (Current Medicinal Chemistry, 2018)
O-Prenyl coumarins (3,3-dimethylallyl, geranyl-, farnesyl- and related biosynthetic derivatives) represent a class of rarely occurring natural products. In the last two decades, such secondary metabolites have been found to possess promising and effective pharmacological properties, mainly in terms of anti-cancer and anti-inflammatory properties. To date, about 160 oxyprenylated coumarins have been extracted from plants, fungi, and bacteria. The genus Citrus has been demonstrated to be among the richest source of the title products. The aim of this comprehensive review is to make a survey of the so far reported literature citations about the main O-prenyl coumarins found in this genus from phytochemical and pharmacological point of views and for which no surveys of the in so far reported literature have been made.
Keywords: Citrus spp. Coumarins